Study the Effects of Microwave Furnace Heat on The Mechanical Properties and Estimated Fatigue life of AA2024-T3 (Journal of Engineering, 2017)
This research aims to study the effect of microwave furnace heat on the mechanical properties and fatigue life of aluminum alloy (AA 2024-T3). Four conditions were used inside microwave furnace (specimens subjected to heat as dry for 30 and 60min. and specimens subjected to heat as wet (water) for 30 and 60 min.), and compared all results with original alloy (AA 2024-T3). Tensile, fatigue, hardness and surface roughness tests were used in this investigation. It is found that hardness of dry conditions is higher than wet conditions and it increases with increasing of time duration inside microwave furnace for dry and wet conditions. Also, tensile strength has the same behavior of hardness, but it increases with decreasing of time. Dry condition for 60 min. shows the higher fatigue strength than other conditions. Surface roughness parameter (Ra) of dry conditions is higher than wet conditions and it decreases with increasing of duration of time.